Total body conditioning for beginners yoga zone (Kuala Lumpur : Vscape Enterprise [distributor])
Total body conditioning distills thousands of years of yoga traditions into simple routines that will leave you feeling refreshed and invigorated. From exercises designed to improve posture and build core strength to stress-releasing and relaxation programs, this is an engaging introduction to the benefits of yoga.Filmed in beautiful Jamaica, this easy-to-follow, integrated mind-body workout is suitable for every fitness level. This video features two complete sessions designed specifically to work together and put you on the road to total fitness.
Keywords: Yoga -- Study and teaching